Republic of Tunisia - Private Sector Assessment Update : Meeting the Challenge of Globalization, Volume 2. Main Report - World Bank (Washington, DC, 2013)
This private sector assessment (PSA) aims at evaluating conditions for private sector development in Tunisia, how they evolved since 1994, and what are the remaining constraints to private investment. It lays out an elaborate framework, placing private sector development in Tunisia, within the context of global economic integration, while facing increased competition from international competitors (particularly those accessing the European market). The analysis of characteristics, and performance of the private sector reveals that although traditionally, Tunisian exports to Europe have been strong, they are now challenged by competition from Asian, and Central/Eastern European countries, a factor exacerbated by the continued anti-export bias of the domestic economy, in light of other countries' rapid investment incentives, which enable private activity to access the opening European market. Thus, improved competitiveness in the country is a major issue. The report proposes reforms in incentives for private sector growth, and in governance; discusses the need, and measures to expand financial access for small/medium enterprises; and proposes options to lay the foundation of a long-term private sector growth strategy. The report contains three volumes, the Executive Summary, and Proposed Reform Agenda; the Main Report; and, Annexes.